„Another World Is Possible” – (Concepts for the Future of Capitalism) - Toshkova, Svetla (Research Papers, 2018)
The study examines the newest tendencies in the development of the economic theories in the context of the radical changes in the structure and methodology of the economic theory in the course of denial of the neoliberal economic model and searching for a new political economic paradigm. It discusses some of the newest concepts of the future of capitalism in which we rediscover the meaning of Marx’s economic theory: about the globalization that he has foreseen and described brilliantly; the ‘explosion’ of capitalism and offensive of the commodity fetishism; the unequal development and concentration of the capital and the conflicts caused by them; the domination of the financial capital and the bursting of the fictitious capital with all the crisis consequences; the subjects of the inequality, exploitation and the critics of the moral principles of the capitalism. Today all these topics are a challenge to a “modern” reading of Marx concerning the problems, boundaries and future of capitalism.
Keywords: Marx; Contemporary economic theories; Future of capitalism